Technology of production and physicochemical properties of activated carbon derived from industrial waste (Chemical Bulletin of Kazakh National University, 2025)
This study examines the specific features of the production technology of granular activated carbon obtained from substandard fine-grained carbon fractions, which are by-products of the special coke industrial production at JSC «Shubarkol Komir.» A technological scheme was developed for producing activated carbon based on this industrial waste, including the methods and conditions for granulation, carbonization, and activation. The physicochemical properties and structural characteristics of the resulting target carbon materials were evaluated. Granular and powdered activated carbons were produced from coke fines with the following composition: 60% coke fines, 35% binder, and 5% chemical activating agent. The temperature dependencies of the activation process were determined. Using adsorption-structural analysis methods, the structure of the activated carbon was studied, revealing a well-developed porous structure that includes mesopores with slit sizes ranging from 2 to 32 nm.
Keywords: carbon materials; activated carbon; sorption properties; activation; coke fines; structural characteristics